Playing a part - Wilke, Daria; Schwartz, Marian, 1951- (New York, New York : Arthur A. Levine Books, an imprint of Scholastic Inc., 2015)
Grishka has grown up in the closed world of a puppet theater in Russia, but now that world seems to be falling apart--his best friend needs an operation, financial difficulties are forcing people out, his homosexual friend Sam, the jester, is leaving for Holland and Grishka no longer knows what role he himself is playing.
Keywords: Marionettes -- Juvenile fiction; Puppeteers -- Juvenile fiction; Puppet theater -- Russia (Federation) -- Juvenile fiction; Gay people -- Russia (Federation) -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Russia (Federation) -- Juvenile fiction; Marionettes -- Fiction; Puppeteers -- Fiction; Puppet theater -- Fiction; Gay people -- Fiction; Identity -- Fiction; Russia (Federation) -- Fiction; LGBTQ YA